Laser-induced breakdown spectroscopy-based quantitative elemental analysis of nutritional and hazardous elements in Solanum nigrum - Shabnam Shahida; Nasar Ahmed; Iqra Ghulam Rasool; Muhammad Imran Khan; Fawad Ahmad; Ansa Madeeha Zafar; Umar Farooq; Mushtaq Hussain Lashari; Khizar Hussain Shah; Abdallah Shanableh; Muhammad Aslam Baig; Rafael Luque (Results in Engineering, 2025)
Medicinal plants play a vital role for the preparation of recently advanced drugs as reservoir of antioxidants and other necessary elements. Therefore, investigating the distinct biodynamic elements of medicinal plants and their evaluation is very important. In this study, laser-induced breakdown spectroscopy was employed for both qualitative and quantitative investigation of different parts of medicinal plant Solanum nigrum and the surrounding soil. Optical emission spectra of soil and different fragments of plant collected from city and village revealed the spectral lines of many nutritional metals including Ca, Mg, Na, K and Fe which are significant for human health, present in relatively large abundance. Moreover, the presence of trace level of a few poisonous substances such as Li, Al, Ba, Si, Ti and Sr in various parts of the plant were found but their concentration was found below the toxic limit of WHO. The authenticity of the qualitative and quantitative detection of the elements in various portions of Solanum nigrum samples by LIBS was endorsed by employing inductively coupled plasma optical emission spectroscopy and its outcomes displayed good agreement with the LIBS data.